On Reading as a Way of Being. Eco ? Rorty ? Barthes - Lindstedt, Krzysztof (INSTED: Interdisciplinary Studies in Education & Society, 2017)
In the article I write about reading as a way of being. My considerations are accompanied by the following questions. What disposition of the interpreter corresponds with open work by U. Eco and how could it support a better understanding of the reading phenomenon? What light can be shed on reading by the means of opening world libraries, as suggested by R. Rorty and chosen aspects of R. Barthes? conception of text reading? In addition, I refer to the controversial theses on the position of books in contemporary times made by J.-F. Lyotard and J. Derrida.